Challenges and opportunities in the Implementation of 5G technology in times of pandemic - Silva-Atencio, Gabriel (2022)
The fifth-generation in telecommunications is already in a very advanced phase in some countries globally, while Latin America is under study and few countries are in the implementation stage; However, there are not only technological and infrastructure challenges that taken into account, for example, current laws and policies, that is why this article analyzes and identifies the challenges and opportunities that must consider in a possible implementation of a prosperous 5G network in Costa Rica. The research had a qualitative approach; therefore, a documentary review of good practices in other countries in Latin America that are carrying out similar processes, together with the tasks and activities carried out to date in Costa Rica. In total, three leading countries in the region identified successfully carrying out their implementation processes in their 5G networks, identifying political, regulatory, and technological challenges. Finally, it concluded that the implementation of 5G is at a very early stage in most countries of the region and Costa Rica. However, significant progress made; it is still in an introductory phase, which represents a considerable threat. for the country in the loss of substantial investment in various industry sectors. It boosts productivity and competitiveness in rural areas.